A Real Determinant of Stock Split Announcements - Hu, May (World Business Institute Australia, 2012)
This paper examines the aggregate determinants of corporate events of stock splits. The evidence shows that good market conditions can drive firms’ decisions to split shares and increase their associated returns. However, the most dominant effect of macroeconomic factors on stock split announcements is business cycle variations. Firms are most likely to split their stocks when they have been experiencing enough excess earnings in economic upturns. This result is more consistent with the Neoclassical Efficiency Hypothesis. This research sheds light on the reasons why we observe corporate events happening in waves and enhance the understanding of why firms split shares at the aggregate level.